Ethnomedical Study of Traditional Medicinal Plants for Cough and Tuberculosis (TB) of the Helong Tribe on Semau Island, Kupang Regency, East Nusa Tenggara - Korassa, Yulius Baki; Blegur, Fatmawati; Sambara, Jefrin; Yuliani, Ni Nyoman; Upa, Satria Mandala Pua (Journal of Comprehensive Science, 2024)
The Helong people in Kupang Regency, NTT Province, have experienced being exposed to cough and tuberculosis (TB). Therefore, it is believed that this community has also long since developed their local knowledge and traditional ways to prevent and treat the disease. In general, this study aims to analyze and find the concept of the Helong Tribe community and ethnomedical practices for the prevention and treatment of cough and tuberculosis (TB). This research is a medical anthropology research using a qualitative research method with an ethnographic approach, which is supported by laboratory research and literature studies. Field research was carried out on Semau Island, NTT Province, involving traditional medicine. The results of the research conducted in the form of interviews with traditional medicine practitioners in the Helong tribe obtained as many as 31 plants used in treatment, and there were 3 plants used to treat cough, including hemorrhagic cough/tuberculosis, namely plants: white banyan (Ficus benjamina L), mesocarp palm fruit (Borassus flabellifer L.) and white flower (Clerodendrum costatum R.Br). The three plants that are suspected to have the ability to treat cough and cough up blood carried out preliminary tests of antibacterial activity against bacteria that generally cause stones, namely Staphylococcus aureus bacteria. The results obtained for ethanol extract of white banyan leaves (Ficus benjamina L) with a concentration of 25% b/v with a diameter of 16.53 mm, 50% b/v with a diameter of 16.33 mm, and 75% b/v with a diameter of 16.56 mm. Mesocarp ethanol extract of palm fruit (Borassus flabellifer L.) At a concentration of 25% b/v with an inhibitory zone diameter of 11.60 mm, a concentration of 50% b/v with an inhibitory zone diameter of 12.30 mm, a concentration of 75% b/v with an inhibitory zone diameter of 13.40 mm, for white flowers (Clerodendrum costatum R.Br) at a concentration of 25%b/v with an inhibitory zone diameter of 9.41 mm, a concentration of 50% b/v of 10.36 mm and a concentration of 75% b/v of 11.24 mm. This means that the three plants have antibacterial activity against Staphylococcus aureus bacteria. Furthermore, for the antibacterial activity test against Mycobacterium tuberculosis bacteria for white banyan plants (Ficus benjamina L.), mesocarp of palm fruit (Borassus flabellifer L.), and white flowers (Clerodendrum costatum R.Br) by the MODS (Microscopically Observed Drug Susceptibility) method, it was obtained that the three plants at concentrations of 250 ppm, 500 ppm, and 1000 ppm were only seen to have the growth of Micobacterium tuberculosis bacteria in the second week. Passive control with INH observation until week IV did not see any bacterial growth, while for negative control in the first week, the growth of Mycobacterium tuberculosis bacteria was seen. It can be concluded that a concentration greater than 1000 ppm is needed for the three plants to inhibit the growth of Mycobacterium tuberculosis bacteria.